A Five Level NPC Inverter Controlled by Using SHEPWM Strategy - Noureddine Ould Cherchali; Abde Abdelhalim Tlemcani; Linda Barazane; Mohamed Seghir Boucherit (Advances in Electrical and Electronic Engineering, 2011)
The object of this paper is to analyse the behavior and the performances of a three-phase induction machine supplied with a five level neutral-point-clamped (NPC) inverter controlled by Selective Harmonic Eliminated Pulse-Width Modulation Technique (SHEPWM). First, the modeling of the inverter and the machine is presented. Thereafter, a theoretical study of the harmonics elimination strategy is detailed; where the genetic algorithm (GA) for elimination purposes is used. After that, this strategy is validated by simulation. Finally, a behavior of the induction machine controlled with this inverter is presented.